Superhard Monoborides: Hardness Enhancement through Alloying in W1−xTaxB. Issue 32 (20th May 2016) - Yeung, Michael T.; Lei, Jialin; Mohammadi, Reza; Turner, Christopher L.; Wang, Yue; Tolbert, Sarah H.; Kaner, Richard B.
Abstract : In tungsten monoboride (WB), the boron atoms are linked in parallel serpentine arrays, with tungsten atoms in between. This lattice is metallic, unlike conventional covalent superhard materials such as diamond or cubic boron nitride. By selectively substituting tungsten atoms with tantalum, the Vickers hardness can be increased to 42.8 GPa, creating a new superhard metal.